PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II D SD NEGERI 132 PEKANBARU - Lisnawati, Nova; Alim, Jesi Alexander; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on May 2015. The data shown the either learning process increased. The basic score of daily examination as 8,20% which 21 students passed and 10 students failed. The ending of daily examination was 67,74% and the average was 74,83% on the passing grade. The second daily examination also increased from basic score as 25% which 27 students passed and 4 students failed. The ending of second daily examination was 87,09% and the average was 86,45. Based on the explanation above it can be concluded that the implementation of realistic mathmaticst education (RME) increased students’ achievement the result of mathematics studies of students II D grade of State Elementary School 132 Pekanbaru.Keywords : Realistic Mathematics Education (RME), Students Achievement The Result Of Mathematics Studies